English Day as a Medium for Introducing Contextual Vocabulary: Teacher Perspective at SMPN 19 Surabaya - Pitaloka, Anna Fadhila; Hanafi, M.; Adriana, Dina (PROJECT (Professional Journal of English Education), 2026)
This study aims to analyze the implementation of the English Day program at SMPN 19 Surabaya as a medium for introducing English vocabulary in context. This study uses a qualitative descriptive approach with data collection techniques through interviews with one English teacher directly involved in this program. The results show that the English Day program is conducted regularly from Tuesday to Thursday and contributes positively to the development of students’ English language skills, especially in terms of vocabulary mastery and speaking skills. Teacher observed that students became more confident when the material presented was relevant to their daily lives. However, obstacles encountered included low students’ participation, lack of motivation, and limited confidence. To optimize this program, teachers suggested increasing the frequency and variety of activities, rewarding students who play an active role, and involving students in planning the English Day program so that it can develop well and become a sustainable school culture. This study also provides input for schools and teachers in the process of optimizing contextual English language learning program. The findings of this study also state that contextual and student-centered learning activities are very important to support the teaching of learning, especially vocabulary.